2020
DOI: 10.1126/sciadv.aaz0510
|View full text |Cite
|
Sign up to set email alerts
|

Computationally aided, entropy-driven synthesis of highly efficient and durable multi-elemental alloy catalysts

Abstract: Multi-elemental alloy nanoparticles (MEA-NPs) hold great promise for catalyst discovery in a virtually unlimited compositional space. However, rational and controllable synthesize of these intrinsically complex structures remains a challenge. Here, we report the computationally aided, entropy-driven design and synthesis of highly efficient and durable catalyst MEA-NPs. The computational strategy includes prescreening of millions of compositions, prediction of alloy formation by density functional theory calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
215
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(220 citation statements)
references
References 45 publications
3
215
0
2
Order By: Relevance
“…11 Löffler et al found that Cr-Mn-Fe-Co-Ni complex solid solution showed at least comparable catalytic activity to Pt in oxygen reduction reaction (ORR), in despite that none of its constituents had good ORR activity. 12 In addition to HEA, other alternative denominations have also been discussed elsewhere, such as complex solid solutions, [12][13][14] multiprincipal element alloys, 15 polyelemental particles, 16,17 multi-elemental alloy, 18 and multimetallic clusters/particles. 19 These kinds of alloys may present a class of promising ideal catalysts having desired activity, stability and selectivity and thus make a paradigm shi in catalysis research.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Löffler et al found that Cr-Mn-Fe-Co-Ni complex solid solution showed at least comparable catalytic activity to Pt in oxygen reduction reaction (ORR), in despite that none of its constituents had good ORR activity. 12 In addition to HEA, other alternative denominations have also been discussed elsewhere, such as complex solid solutions, [12][13][14] multiprincipal element alloys, 15 polyelemental particles, 16,17 multi-elemental alloy, 18 and multimetallic clusters/particles. 19 These kinds of alloys may present a class of promising ideal catalysts having desired activity, stability and selectivity and thus make a paradigm shi in catalysis research.…”
Section: Introductionmentioning
confidence: 99%
“…19 These kinds of alloys may present a class of promising ideal catalysts having desired activity, stability and selectivity and thus make a paradigm shi in catalysis research. 20 These alloy catalysts with appealing performances have been reported recently, [10][11][12][17][18][19][21][22][23][24] yet, the interpretation on their properties is still challenging. Quite recently, Rossmeisl and co-authors have made a great step in theoretically predicting ORR 25 and CO 2 and CO reduction 26 properties on HEAs by combing density functional theory calculations and supervised machine learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite recently, they applied theoretical computation to facilitate the rational design of HEA-NPs. [81] Prescreening millions of compositions was performed before practical synthesis of HEA-NPs via CTS method, density functional theory (DFT) calculations were carried out to predict their formation energies, while a hybrid Monte Carlo and molecular dynamics (MC-MD) approach was implemented to stimulate their formation process both thermodynamically and kinetically. This computational strategy provides rational guidance for HEA-NPs design and saves substantial time and laboratory work from experimentally exploring an actually unlimited compositional space.…”
Section: Carbothermal Shock Methodsmentioning
confidence: 99%
“…High-entropy alloys (HEAs) have demonstrated significant potential applications in many fields due to their unique and fascinating properties [16][17][18][19][20] . Thus, HEAs have recently garnered increased attentions and become one of the hottest materials.…”
Section: Introductionmentioning
confidence: 99%